The mucocutaneous manifestations of sulfur mustard gas on 1024 Iraqi victims: ISIS chemical attack in the South of Kirkuk. (3rd July 2022) - Emadi, Seyed Naser; Abtahi-Naeini, Bahareh; Rahmat Pour Rokni, Ghasem; Emadi, Seyed Emad; Hamzelou, Shahin
Abstract: The aim of this study is to evaluate the frequency and the distribution of symptoms and complications of oculocutaneous and respiratory systems among the individuals with a history of toxic exposure to probably sulfur mustard (SM) gas in Kirkuk, Iraq by the Islamic State of Iraq and Syria (ISIS) also known as "Daesh." In this cross-sectional study, victims of chemical weapons used by Daesh in TazaKhurmatu, Kirkuk, Iraq on March 9 2016 were evaluated 2 days after exposure by the Iranian medical team, with a focus on skin, eye, and lung lesions using a standardized medical evaluation sheet. A total of 1024 Iraqi who are of the ages 2 through 86 claimed exposure to SM were evaluated. Of this number, 480 were male (46.87%) and 544 patients were female (53.13%). We found 66 and 30 subjects who had a moderate or severe injury on cutaneous, ocular, and respiratory organs respectively. The cutaneous injury was the most severe medical complaint, and 24 cases had severe skin lesions including erythema, bulla, and necrosis in folds (groin and genitalia), and the dependent areas. The evidence of environmental contamination with mustard gas includes the smell of garlic odor and the presence of black oil in the environment (ground, soil, and wall). The high number of chemical victims with severe skin lesions rather than eye and lung lesions can be attributed to the transformation of mustard gas to the liquid form at low temperatures in the winter season in Kirkuk. Additionally, increased skin lesions in the buttock and lumbosacral area were probably owing to indirect exposure to the contaminated tools and environment.